Cost-Effective TA Cloning Applied to Sanger Sequencing and HLA Allele Typing - NEDUVAT, Anupama Cheleri; MURTHY, Prerana Madhusudhana; SUNDARRAJAN, Sudarson; PADMANABHAN, Sriram (Walailak Journal of Science and Technology (WJST), 2019)
Polymerase chain reaction (PCR)-based technology for clinical HLA typing involves DNA Sanger sequencing of the PCR amplified products of polymorphic loci of HLA, such as HLA-A, -B, -C, -DPB1,-DQB1, and -DRB1, in support of unrelated donor hematopoietic stem cell transplantation. The TA cloning of all the amplicons, followed by Sanger sequencing, provides a primary screening tool of potential organ donors, or to identify individuals who might have potential adverse drug responses. The Class I exon 2 and 3 genes of HLA was amplified as a single fragment and cloned into a TA cloning vector pTZ57R/T, while the Class II exon 2 and 3 amplified fragments were added together in a ligation mix with the vector pTZ57R/T. Positive clones were subjected to Sanger sequencing, and HLA alleles determined using the IMGT database. Results indicate that all the exons of the HLA genes by could be cloned by the strategies described. Furthermore, we were also successful in achieving the amplification of all the desired amplicons as a multiplex PCR, thereby reducing the cost of the modified method further by almost 60 %. We present a cost-effective TA cloning strategy for achieving accurate allele typing of HLA at 2- digit resolution. Taken together, an efficient cloning methodology with a significant lower cost for accurate HLA typing presented here is encouraging. The data suggests that it may be employed for routine cloning of variable targets in molecular biology applications.